Diffusion of Innovation: The Perception and Attitude of Journalists in South-South Nigeria on e-Governance: Array - Okon, Patrick Ene; Ndukwe, Cosmos Chukwudi; Nweke, Chidinma Joan; Okugo, Uzoma Chukwuemeka (Acta Universitatis Danubius. Communicatio, 2020)
The major focus of this study was to assess the attitude and perception of practising journalists towards e-governance in South-South Nigeria, with Cross River and Akwa Ibom States as the case study. The theoretical framework hinged on the diffusion of innovation theory. Descriptive survey method was used. Out of a population of 702 practising journalists in the two states, 140 of them formed the study’s sample. Questionnaire was the instrument used to generate data. Findings showed that majority of the respondents had a poor attitude towards e-governance as they did not access government information, participate in e-governance process and report/cover e-governance even though they had a positive perception of the innovation and its operations. It was, therefore, recommended that journalists should periodically upgrade their knowledge of this innovation in governance as well as participate actively in publicising it to the populace.